2014
DOI: 10.1038/onc.2013.579
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor-B enhances estrogen responsiveness of breast cancer cells via scaffolding PELP1- and estrogen receptor-containing transcription complexes

Abstract: Progesterone and estrogen are important drivers of breast cancer proliferation. Herein, we probed ER-alpha and PR cross-talk in breast cancer models. Stable expression of PR-B in PR-low/ER+ MCF7 cells increased cellular sensitivity to estradiol and IGF1, as measured in growth assays performed in the absence of exogenous progestin; similar results were obtained in PR-null/ER+ T47D cells stably expressing PR-B. Genome-wide microarray analyses revealed that unliganded PR-B induced robust expression of a subset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(137 citation statements)
references
References 48 publications
7
127
0
3
Order By: Relevance
“…The master regulator of progesterone response in breast cancer appears to be estrogen dependent which regulates PR abundance, thereby permitting PR-DNA binding, which suggests that the action of estrogen and progesterone is inextricably linked. ER and PR have the longest co-existence in relation to other receptors such that ERa-mediated up-regulation of PR abundance permits activity in response to progesterone, and PR in turn regulates a subset of ERa actions [28,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The master regulator of progesterone response in breast cancer appears to be estrogen dependent which regulates PR abundance, thereby permitting PR-DNA binding, which suggests that the action of estrogen and progesterone is inextricably linked. ER and PR have the longest co-existence in relation to other receptors such that ERa-mediated up-regulation of PR abundance permits activity in response to progesterone, and PR in turn regulates a subset of ERa actions [28,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of both estrogen and progesterone, PGR was shown to be recruited to the ESR1 complex and to redirect ESR1-binding events, resulting in a gene expression profile associated with better clinical outcome (Mohammed et al 2015). However, in the presence of estrogen alone, un-liganded PGRB activated a subset of ER target genes by acting as a molecular scaffold for the formation of a transcriptional complex with ESR1 and PELP1, resulting in a more aggressive proliferative response to estrogen (Daniel et al 2015). It is likely that the action of ESR1 and PGR and their crosstalk are highly context dependent.…”
Section: Combinatorial Control Of Gene Expression By Nrs In Breast Camentioning
confidence: 99%
“…[68][69][70] In 2015, researchers 67 conducted a comparative study by IHC on the sensitivity of PELP1, compared with GATA3, in TNBC tissues. They found that, of the 70 TNBC tumors, 67 (96%) showed strong, diffuse nuclear staining for PELP1, whereas only 46% (32 of 69) of the tumors were positive for GATA3 (the tissue from one case did not survive processing) (P , .001).…”
Section: Diagnostic Utility Of Gata3 In Tnbcsmentioning
confidence: 99%